Evaluation of Pentoxifylline and Colchicine Administration on Clinical Outcomes of Hospitalized Patients with COVID-19 - AR Eghbali; F Ahmadpour; F Ahmadpour; M Birjandi; J Khalili Fard; M Abbasinasab; F Fakoori; H Shayestehyekta (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2023)
Background and Objective: The COVID-19 pandemic has caused numerous cases of respiratory failure and death. Due to the little information available about the disease treatment, we decided to evaluate the effectiveness of pentoxifylline and colchicine in preventing the progression of the disease to the stage of deterioration in hospitalized patients with COVID-19. Methods: In this double-blind randomized clinical trial, 120 patients (60 in the control group and 60 in the intervention group) with COVID-19 over 40 years of age with moderate and severe disease were examined in Shafa Khorramabad Hospital. The intervention group received pentoxifylline at a dose of 400 mg every 12 hours and colchicine at a dose of 0.5 mg daily in addition to standard treatment, and the control group received the standard treatment regimen alone. In both groups, clinical and laboratory criteria in blood were compared. Also, the duration of hospitalization, the duration of the intensive care unit admission, the rate of recovery (reduction of disease symptoms and increase of blood oxygen), and death were compared. Findings: There was no significant difference between the age, weight, gender, medical history and early symptoms of the two groups. The two groups differed significantly in the number of people hospitalized in the ICU (17 patients, 28.3% in the control group) and (6 patients, 10% in the intervention group) and the number of people with persistent fever (24 patients, 30% in the control group), and (12 patients, 20% in the intervention group) (p<0.05). However, there was no significant difference between the two groups in terms of mortality, clinical and laboratory results. Conclusion: Based on the results of this study, prescribing the two drugs, pentoxifylline and colchicine, may prevent the critical stage of the disease.